2022
DOI: 10.1111/bjd.21649
|View full text |Cite
|
Sign up to set email alerts
|

The effect of screening on melanoma incidence and biopsy rates

Abstract: Background Cutaneous melanomas are common cancers in white‐skinned populations, and early detection is promoted as a means of reducing morbidity and mortality. There is concern that increased skin screening is leading to overdiagnosis of indolent melanomas with low risk of lethality. The extent of melanoma overdiagnosis associated with screening is unknown. Objectives To estimate possible overdiagnosis by comparing subsequent melanoma incidence and biopsy rates among people subjected to skin screening those wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…14 and references therein]; a large recent Australian study revealed about 60% in situ melanoma tumors (low-Treg tumors) at diagnosis. 40 …”
Section: The Seasonal Variation In Cancer Incidence Rate and Prognosismentioning
confidence: 99%
“…14 and references therein]; a large recent Australian study revealed about 60% in situ melanoma tumors (low-Treg tumors) at diagnosis. 40 …”
Section: The Seasonal Variation In Cancer Incidence Rate and Prognosismentioning
confidence: 99%
“…18,23 A systematic literature review and field studies have confirmed that the implementation of skin cancer screening interventions leads to an increase in the incidence of in situ and thin CMM. 24,25 Other researchers have reported data at variance with the hypothesis of a key role of overdiagnosis in incidence trends. In the Netherlands, for example, the rates of both thin (≤1.0 mm) and thick (>4.0 mm) CMM have increased, accompanied by an increase in mortality too.…”
Section: Introductionmentioning
confidence: 99%
“…Using a propensity score‐based analysis, they obtained results that may approximately mimic those from a trial of melanoma screening. 1 Participants who had a prior clinical skin examination were 30% more likely have a new diagnosis of melanoma than controls. Those who had a skin biopsy in the first year of follow‐up were 50% more likely.…”
mentioning
confidence: 98%
“…In practice, the predictors of biomarkers will need to be assessed alongside clinical phenotypic and demographic factors. 1 Biomarkers can potentially help us with the prediction of the cause of a disease, its progression, regression, outcome, diagnosis and, in the case of the scoping review in this issue of the BJD, 2 the results of treatment. However, the sheer volume of the biomarker literature is in stark contrast to the few biomarkers that have established utility in clinical practice, 3 especially in inflammatory disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation